Discrepancy between Forward and Reverse Seepage Characteristics in a Single Rough Fracture. (22nd March 2021) - Niu, Yulong; Wang, Yuan; Sun, Zhiyu; Li, Jinghua; Xiang, Xin; Wang, Zhikui
Abstract : Under the uniform seepage boundary condition, the forward and reverse seepage flow rates will vary widely. In response to this phenomenon, this paper studies the mechanism of the difference in seepage characteristics between the forward and reverse directions from the fracture profile's roughness, Darcy and non-Darcy seepage, and distribution of eddy currents. First of all, wavelet transform was used to decompose and reconstruct the single rough fracture for 8 times, and then 9 fracture models with various roughness degrees were constructed. Then, Finite Volume Method was used to simulate the seepage in the original and approximate models of the Reynolds number varying from 0.001 to 1000. The results show that the nonlinear seepage is necessary for the difference between the forward and reverse seepage characteristics of the single rough fracture. The mechanism of the discrepancy between forward and reverse nonlinear seepages is the diverse shapes and distribution of the eddy current generated by the forward and reverse seepage. The secondary roughness provides space for the existence and development of the eddy current. The secondary roughness is the geometric basis of the discrepancy between the forward and reverse seepage characteristics.